Swallowing characteristics of patients with COVID-19 with and without intubation. Scoping review - Leguizamo Galvis, Paola; Perdomo, Mónica; Dussán Cuenca, Bleydis; Ramírez, Pilar; Morales, Mónica (Revista de Investigación en Logopedia, 2023)
COVID-19 or SARS-CoV-2 is an infectious disease caused by the most recently discovered coronavirus, which has been the cause of the last recorded pandemic for humanity; Its rapid diffusion and progression required novel approaches in clinical practices, where the speech therapist has become increasingly visible, due to the commitments that these patients present at the swallowing level. The objective of this review is to determine the swallowing situation of post-covid patients with and without intubation through the exploration of the scientific evidence of the exploratory systematic review of the literature, under the standards of the PRISMA methodology and the structure PSALT. Observing that 50% of the articles included are of an observational, descriptive, prospective type, with a greater number of publications in the year 2021, related to the highest peak of the pandemic generated by the Sars Cov 2 virus. Within the variables analyzed, it is observed that the speech-language assessment is carried out in three spheres; instrumental, clinical and self-report, the FEES, the FOIS scale and the EAT-10 scale are the most frequently used. Patients who are infected with SARS COV-2 and require orotracheal intubation are characterized by multiple concomitant factors that promote penetration and silent aspiration of food. Similarly, in patients who do not require support with mechanical ventilation, the COVID 19 virus can cause, although with a lower incidence, alterations in swallowing function as a result of the neuronal damage produced by this pathogen.